Should we consider assessment of bone mineral density earlier in postmenopausal women with pelvic organ prolapse? - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2011)
Objective To investigate a possible association between the presence of pelvic organ prolapse and osteopenia or osteoporosis in early postmenopausal women. Design Eighty-seven postmenopausal women between the ages of 55 and 60 years who had been admitted to the Gynecology or Menopause Outpatient clinics of Marmara University, School of Medicine were included in the study. Quantification of pelvic organ prolapse was performed for each patient. The bone mineral density measurements of the lumbar vertebrae by dual-energy X-ray absorptiometry were compared between the groups with and without pelvic organ prolapse. Results The mean T-scores for the lumbar area for women with or without pelvic organ prolapse were comparable between the study groups. Conclusions It appears that presence of pelvic organ prolapse in early postmenopausal women is not helpful in predicting osteoporosis.
Keywords: PELVIC ORGAN PROLAPSE; OSTEOPOROSIS; POSTMENOPAUSE; URINARY-INCONTINENCE; OLDER WOMEN; FRACTURE; RISK; POPULATION; AGE; THRESHOLDS; PREVALENCE